Letramento crítico e questões de identidade em textos digitais no livro didático de língua inglesa. - Baladeli, Ana Paula Domingos (2013)
The teaching material has a relevant role in the language teaching and its discourses can promotes or not, the maintenance of mistaken representation of sociocultural identities. In front of the historical fact of the National Textbook Program distributes for the first time textbook for English subject to the high school, we select these material, as research object based on New Literacies Studies (STREET, 1995, 2003; KLEIMAN, 1995) and Critical Literacy (CANAGARAJAH, 1999, 2009; PENNYCOOK, 1994, 2006; MOITA LOPES, 1996, 1998, FERREIRA, 2000, 2001). In globalization and spread of digital technologies context the sociocultural identity issue has been highlighted as emergent topic in the teaching and learning process of foreign language, therefore it is urgent concern ourselves about the representations published through the digital texts. The identity conception as social production, fluid, hybrid and in constant construction (HALL, 2003, 2006; WOODWARD, 2009) supports this basic and documental research which proposal is analyses in the digital texts from English textbooks, the literacy model and the representations of sociocultural identities. Therefore, we based on Content Analyses (BARDIN, 1977) and on Critical Discourse Analysis (FAIRCLOUGH, 1989, 2001) in order to identity the representations about Brazilian people and about to be Brazilian in five digital texts select from two didactic collections. Based on autonomous and ideological models by Street (1995), the analysis of the five digital texts selected from Links: english for teens e Keep in Mind collections based on Street (1995) illustrated in higher frequency; the use of non authentic texts in the units; reading proposals based on autonomous model of literacy and, they were categorizes under stereotypical/prejudiced and hypothetical/fictitious with superficial treatment to the Transversal Themes; stereotypes and mistaken representations about Brazilian people and about Brazil. In lower frequency, the ideological model of literacy was identified in the libertatory/critical category with the problematization of digital texts themes; the contestation of the representation published on text and reading activities and for enabling the appreciation of student sociocultural background. The results indicates that every didactic material needs to be problematized by the teacher in order to become the English classroom a positive space to the identities students construction through the appreciation of the sociocultural diversity.